Living with cancer and multimorbidity: A qualitative study of self-management experiences of older adults with cancer. (August 2021) - Haase, Kristen R.; Hall, Steven; Sattar, Schroder; Ahmed, Shahid
Abstract: Purpose: Older adults are most commonly diagnosed with cancer but needs related to managing multiple chronic conditions (multimorbidity) are often overlooked. Although self-management is a growing imperative in cancer care, the experiences of older adults managing multimorbidity alongside a cancer diagnosis have been less explored. In this study we interviewed older adults with cancer and multimorbidity to understand their experiences with cancer self-management while living with multimorbidity. Methods and Sample: We used a descriptive qualitative approach and interviewed older adults (n = 14) about their experiences and had them complete the Multimorbidity Treatment Questionnaire; qualitative data were analyzed using thematic analysis. Results: We identified three themes, including: Situating cancer and aging: personal, illness, and caregiving experiences; enacting and engaging in self-management; and challenges of living with cancer and navigating multimorbidity. Older adults demonstrated many strengths in engaging in self-management work but faced many challenges as they navigated the siloed healthcare system. Conclusion: Oncology nurses play a critical role in supporting self-management for older adults with cancer. We propose that more in-depth research is needed to explore older adults' experiences with cancer self-management to ensure that they are able to engage in the self-management that is required in our healthcare system. Highlights: Older adults find cancer self-management is complicated by multimorbidity Older adults engaging and enacting cancer self-management draw on existing skills We need more supports for older adults living with cancer and chronic disease